2000
DOI: 10.1074/jbc.m002739200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues within Two Regions Involved in Self-association of Viral Histone-like Protein p6 from Phage Ø29

Abstract: Protein p6 of Bacillus subtilis phage Ø29 is involved in the initiation of viral DNA replication and transcription by forming a multimeric nucleoprotein complex with the phage DNA. Based on this, together with its abundance and its capacity to bind to the whole viral genome, it has been proposed to be a viral histone-like protein. Protein p6 is in a monomer-dimer-oligomer equilibrium association. We have identified protein p6 mutants deficient in self-association by testing random mutants obtained by degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Thus, the capability of p6NÁ5 and p6NÁ13 deletion mutants to selfassociate was tested in vitro by glutaraldehyde crosslinking. Dimer formation was highly impaired in p6NÁ5, and undetectable in p6NÁ13 (Abril et al, 2000). Therefore, the observed self-association deficiency explains the DNA binding impairment of p6NÁ5 and p6NÁ13, suggesting that the N-terminal region, in addition to DNA binding, is involved in dimer formation.…”
Section: Protein P6 Mutants Deficient In Self-associationmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the capability of p6NÁ5 and p6NÁ13 deletion mutants to selfassociate was tested in vitro by glutaraldehyde crosslinking. Dimer formation was highly impaired in p6NÁ5, and undetectable in p6NÁ13 (Abril et al, 2000). Therefore, the observed self-association deficiency explains the DNA binding impairment of p6NÁ5 and p6NÁ13, suggesting that the N-terminal region, in addition to DNA binding, is involved in dimer formation.…”
Section: Protein P6 Mutants Deficient In Self-associationmentioning
confidence: 91%
“…Mutant p6A44V, located at the central part of the protein, showed impaired dimer formation ability, and a reduced capacity to bind DNA and to activate the initiation of Ø29 DNA replication. More dramatic was the phenotype of mutant p6I8T, which had a self-association capacity reduced at least 10-fold and did not bind DNA nor activate Ø29 DNA initiation of replication (Abril et al, 2000).…”
Section: Protein P6 Mutants Deficient In Self-associationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to impaired dimer formation ability, mutations at these two residues showed reduced DNA binding affinity and they were affected in the initiation of 29 DNA replication. Thus, dimers seem to be the active form of 29 DBP for DNA binding (Abril et al, 2000).…”
Section: Replication Origins Of Tp Containing Genomesmentioning
confidence: 97%
“…Structure-function work on p6 indicated that the N-terminal region of the protein plays a role in both DNA binding (Otero et al, 1990 ) and dimer formation (Abril et al, 2000 ). By site-directed mutagenesis, it could be disclosed that residues Ile8 and Val44 are directly involved in protein dimer formation (Abril et al, 2000 , 2002 ), whereas Lys2, Lys10 and, especially, Arg6, are essential for DNA binding in vitro and viral DNA synthesis in vivo (Bravo et al, 1994b ; Freire et al, 1994 ).…”
Section: A Histone-like Protein Encoded By Bacteriophage φ29mentioning
confidence: 99%